Bin Laden the man who declared war on America - Bodansky, Yossef (Rocklin, Calif Forum, 1999)
Who is Osama bin Laden - the only terrorist leader ever to have declared a holy war against America? What drives him and those he leads to hate a West that helped educate, enrich, and arm them? In meticulous detail, terrorism expert Yossef Bodansky uncovers the events in bin Laden's life that turned the once-promising engineering student into a cold-blooded leader of radical Islam. Including new information about bin Laden's pursuit of chemical, biological, and nuclear weapons, covert deals between the U.S. and Islamic terrorists, and American foreign policy blunders that have cost countless lives, this book is a sobering wake-up call
Introduction: The Inevitable Struggle -- 1. The Radicalization of an Engineer -- 2. Crisis and Rebirth -- 3. Triumph over the Paper Tiger -- 4. Emir bin Laden -- 5. Inciting the Revolution -- 6. The Committee of Three -- 7. Declaration of War -- 8. New Allies in the War -- 9. The U.S. Embassy Bombings -- 10. Humiliating the Enemy -- 11. Strengthening the Arsenal -- 12. The Bin Laden Plans -- 13. What's Next?
Includes bibliographical references (p. 413-417) and index
1
Keywords: Bin Laden, Osama -- 1957-2011; Jihad; Muslims -- Saudi Arabia -- Biography; Terrorism -- Religious aspects -- Islam; Terrorists -- Saudi Arabia -- Biography